PERAN MEDIA DALAM UPAYA MENINGKATKAN PENGETAHUAN DAN TINDAKAN PENCEGAHAN CORONAVIRUS DISEASE (COVID 19) - Naris Dyah Prasetyawati; Sigid Sudaryanto; Desif Upix Usmaningrum (Sekolah Tinggi Pariwisata Mataram, 2021)
One of the positive values of development is the flexibility to access information. Information is needed by everyone with various purposes, including updating knowledge, material for opinions and making decisions. In the field of health, information that is developing is very diverse. Starting from preventive, curative and rehabilitative measures. Disseminating health information is something that must be done carefully. Delivering information in the health sector is not easy to do. Currently, wireless communication networks have spread to almost all area. So that it can be used for the process of disseminating health information to people anywhere and anytime more actively, independently and responsibly. The purpose of this study is to determine the role of the media in an effort to increase knowledge and actions taken by the community in efforts to prevent COVID19 in society. The research used descriptive research method where primary data were collected online using google form. The results of this study the public prefers to access news from electronic sources than non-electronic ones or from health promotion officers. However, through online news there has been a lot of less accurate and counter-productive news, This raises separate concerns about the truth and the party responsible for the news or information. It is better if as consumers of information we are wiser in responding by filtering the information received before passing the information on to other community groups. We should also look for other sources of information that are more validated so that they are not wrong in making decisions. Conclusion media research can increase public knowledge if used appropriately and responsibly. Information that comes from the media is also used as the basis for taking action by the community. The combination of extension methods that are mass gathering or using leaflets and brochures can be combined in the form of digital outreach, for example with short videos or sharing information through other social media which is more efficient, creative and in line with the target recipients of information.